Search for the wild animal reservoir of Trypanosoma sp in mammals of N’Djili-Brasseries (Kinshasa, Democratic Republic of Congo) - M.W. Kabamba Mwamba; G. Tshilenge; J. Malekani (Institut Agronomique et Vétérinaire Hassan II, 2018)
During 6 months, 201 specimens of wild mammals representing 7 species divided into 6 genera, 4 families and 3 orders, of which 2 Genetta angolensis, 3 Nandinia binotata, 10 Galagoides demidoff, 35 Protoxerus strangeri, 73 Funisciurus congicus, 15 Rattus rattus and 63 Rattus norvegicus, were captured at N’Djili- Brasserie to identify the wild animal reservoir of trypanosoma. This study revealed by using the method of polymerase chain reaction (PCR) that among these seven species, only Rattus rattus and Rattus norvegicus, captured in the area inhabited by man, had Trypanosoma brucei gambiense with a prevalence of 13.3% for Rattus rattus and 9.5% for Rattus norvegicus. This lead us to conclude that these two species would be reservoir of Trypanosoma brucei gambiense.